Acute coronary syndromes in low- and middle-income countries: Moving forward. (August 2016) - Seligman, Benjamin; Vedanthan, Rajesh; Fuster, Valentin
Abstract: Cardiovascular disease remains the leading cause of death worldwide, particularly in low- and middle-income countries (LMICs), with substantial mortality from acute coronary syndromes. These deaths, when compared against high-income countries, occur at younger ages, and, beyond the lives lost, often result in economic privation for families deprived of a breadwinner and indebted by the oftentimes catastrophic cost of inpatient medical care. This burden will likely grow in scale in the years ahead as more countries pass through the epidemiologic transition. Billions around the world are beginning to experience the comforts that even modestly increased incomes can provide, including diets high in fats and sugars, more sedentary lifestyles, and tobacco and alcohol use and abuse. Health care systems in many of these countries are ill-equipped to prevent the harms caused by these lifestyles, as well as treat the acute coronary syndromes that result from them—including insufficient access to appropriate facilities and medications, difficulties with transport, and low awareness of the symptoms and need for emergent evaluation.